PENERAPAN PEMIKIRAN EKONOMI ISLAM ABU UBAID TERHADAP PEREKONOMIAN MODERN DI INDONESIA - Syakila Novia Fitri; Salsabila, Salsabila; Sopia Mayang Sari; Ahmad Wahyudi Zein (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This research discusses Islamic economic thought according to a Muslim scholar named Abu Ubaid and its relevance in Indonesia. Using a library research method that gathers relevant information related to the topic or problem being researched, this study attempts to reveal the relevance of Abu Ubaid’s economic thought in the modern economic system in Indonesia. One of the scopes that can be seen in his monumental work titled Kitab al-Amwal. The concept of justice becomes the basic principle of economics that he promotes as a strong philosophical foundation in building the foundation of economic thought. The concept of justice is always contained in every thought, both related to individual rights, public rights, and the rights of the state as the instrument of the highest authority. So with the spirit of the philosophical foundation promoted by Abu Ubaid, it certainly becomes a concept of the economic order of the state. One of which has been implemented in Indonesia as a sovereign state through the grains of the 1945 Constitution as the highest source of law. So when public interest becomes the main priority above all other interests, it will certainly give birth to a concept of justice that produces a balance of individual, public and state rights, and will certainly lead to a harmonious economic concept order accompanied by the achievement of community welfare.